Mengungkap makna angka: perjalanan sejarah angka nol dari india melalui dunia islam sampai ke eropa - Rahmawati, Siti (Maliki Interdisciplinary Journal, 2026)
This study examines the journey of zero and the number system in the development of mathematics. Zero not only serves as a position marker but also becomes a very important scientific knowledge. This article traces the origins of zero in India, which eventually developed and spread widely to the Islamic world and Europe. In India, mathematicians introduced zero as a symbol and concept that played a crucial role in the number system and calculation. This concept was then carried and further developed, finally being accepted by scientists in the Islamic world. Zero developed and spread through trade routes, scientific centers, and manuscript translators, finally reaching Europe in the Middle Ages. This process of dissemination shows that the development of zero was the result of collaboration across civilizations. This long journey demonstrates that zero and the number system are not merely empty symbols, but are crucial components that enabled the development of mathematics. By understanding its history, we can see how a simple idea can have a profound impact on the development of global science.